2009
DOI: 10.3846/1648-4142.2009.24.288-295
|View full text |Cite
|
Sign up to set email alerts
|

Saturation Flow Versus Green Time at Two‐stage Signal Controlled Intersections

Abstract: Abstract.Intersections are the key components of road networks considerably aff ecting capacity. As fl ow levels and experience have increased over the years, methods and means have been developed to cope with growing demand for traffi c at road junctions. Among various traffi c control devices and techniques developed to cope with confl icting movements, traffi c signals create artifi cial gaps to accommodate the impeded traffi c streams. Th e majority of parameters that govern signalised intersection control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Boumediene et al . found that saturation flow rate decreased slightly with growing green time. HCM 2000 also supported that the saturation headway might rise when the length of green time exceeds 50 seconds .…”
Section: Past Researchmentioning
confidence: 93%
“…Boumediene et al . found that saturation flow rate decreased slightly with growing green time. HCM 2000 also supported that the saturation headway might rise when the length of green time exceeds 50 seconds .…”
Section: Past Researchmentioning
confidence: 93%
“…Traffic safety problems, such as the interaction between a motor vehicle and road guardrails, motor vehicle dynamics and guardrails of various types were investigated in different time periods by Antov et al (2009), Beljatynskij et al (2009), Boumediene et al (2009), Çalışkanelli et al (2009), Cansiz and Atahan (2006), Coon and Reid (2005), Dragčević et al (2009), Elvik et al (1997), Ibitoye et al (2006), Junevičius and Bogdevičius (2009), Kapski et al (2008), Kinderytė-Poškienė and Sokolovskij (2008), Lazda and Smirnovs (2009), Macek and Měšťanová (2009), Nagurnas et al (2008), Pelenytė-Vyšniauskienė and Jurkauskas (2007), Prentkovskis et al (2007;2009), Sokolovskij et al (2007), Šliupas (2009), Tautkus and Bazaras (2007), Vansauskas and Bogdevičius (2009), Viba et al (2009), Vorobjovas and Žilionienė (2008), etc.…”
Section: Purposes Of Road Guardrails and Overview Of Research Studiesmentioning
confidence: 99%
“…Using the cellular automaton (CA) model it is possible to describe the complex, global and coherent systems and nonlinear phenomena using simple rules. CA models are discrete, which, by their nature, are strictly determined and obeying various laws, but their behaviour can be so complex that it is sometimes difficult to distinguish it from stochastic processes, and the same process may seem chaotic and unpredictable (Boumediene et al 2009;Gowri, Sivanandan 2008;Lárraga et al 2005).…”
Section: Introductionmentioning
confidence: 99%